Use of Internet Resources and Services: A Review of LIS Literature - Maheswarappa, B. S.; Tadasad, P. G.; Emmanuel Ebnazar, C.; Alur, Seema A. (Journal of Information and Knowledge, 2002)
Reviews the literature in LIS on the use of Internet resources and services in different settings in two sections viz: foreign and Indian literature. Concludes that despite the growth in the number of users the studies in LIS regarding the use of Internet resources and services in different settings are at their infancy.